P592 Costs savings associated with ferric maltol and the reduced use of intravenous iron based on real world data. (27th May 2021) - Howaldt, S; Becker, C K; Becker, J A; Poinas, A C
Abstract: Background: Intravenous (IV) iron is frequently used in patients with iron deficiency (ID) when conventional oral ferrous products are ineffective or cannot be used (e.g. due to poor tolerability). Oral ferric maltol is a new iron ferric product registered in Europe and US. The aim of this study was to quantify the use of IV iron before and after the introduction of the new oral ferric maltol in real world settings and extrapolate the overall costs involved. Methods: Data were collected from a single centre German clinical practice, MVZ für Immunologie, in inflammatory bowel disease (IBD) patients treated with iron therapy for ID with or without anaemia between 2013 and 2019 through the systematic CEDUR IBD registry and local medical records. The first cohort was formed of patients treated between 2013 and 2015, receiving only IV iron as ferric carboxymaltose (FCM). The second cohort was formed of patients treated between 2017 and 2019, receiving either oral ferric maltol only or ferric maltol in combination with FCM. Costs involved in each cohort were extrapolated using a societal perspective. Results: Following the introduction of oral ferric maltol, the actual total number of FCM infusions observed was 138, showing a decrease of 70% compared to the first cohort in which oral ferric maltol was not available. This decreased number of infusions between the two cohorts was associated with total costs-savings of €56, 933. In the first cohort, the administration costs were €44, 536, the drug acquisition costs were €59, 536 and the productivity loss were €30, 944. In the second cohort, the administration costs were €13, 597 the drug acquisition costs were €55, 028 and the productivity loss were €9, 447. A secondary scenario strictly applying the doses taken from respective SmPCs was tested and resulted in greater costs-savings. Noteworthy, the mean (SD) haemoglobin (Hb) level at baseline in the first cohort was lower with 11.5g/dl (1.19) vs. 12.2g/dl (1.18) in the second cohort. Three to six months after the treatment had been stopped, the mean (SD) Hb level was 13g/dl in both the first and second cohort with a SD of 1.31 and 1.37 respectively, showing that Hb levels were maintained in both cohorts. Conclusion: The introduction of the new oral ferric maltol resulted in a decrease of 70% in terms of number of FCM infusions which was associated with costs-savings of €56, 933 in terms of administration, drug acquisition and productivity loss costs. Considering that Hb levels were maintained in both cohorts, these results indicate that ID patients with or without anaemia previously treated with IV iron can also be managed effectively with oral ferric maltol resulting in overall societal cost-savings.